L1 TGF-beta blocks type I IFN release and tumor rejection in spontaneous mammary tumors. (1st October 2020) - Bercovici, N; Guérin, MV; Regnier, F; Weiss, JM; Feuillet, V; Vimeux, L; Altan-Bonnet, G; Donnadieu, E; Trautmann, A
Abstract : Background: Activation of the STimulator of INterferon Genes (STING) by DMXAA (5, 6-dimethylxanthenone-4-acetic acid) can induce a strong production of IFNα/β and the rejection of transplanted primary tumors. However, the efficacy of such therapeutic approach for the treatment of spontaneous tumors had still to be evaluated. Material and Methods: We have tested whether the injection of DMXAA or other STING agonists and TLR4 agonist, could lead to the regression of spontaneous MMTV-PyMT mammary tumors. We also characterized, in time and space, the early signaling events triggered downstream STING and the distribution of infiltrating immune cells in the tumor microenvironment by fluorescence imaging. Results: We show that spontaneous MMTV-PyMT mammary tumors are resistant to immunotherapeutic intervention. We demonstrate that TGFβ, abundant in spontaneous tumors, is a key molecule limiting this IFN-induced-tumor regression by DMXAA. Mechanistically, we found that TGFβ blocks the phosphorylation of IRF3 and the ensuing IFNα/β production by tumor infiltrating macrophages. Finally, blocking TGFβ restores the production of IFNα by activated MHCII + tumor-associated macrophages, and enables tumor regression induced by STING activation. Conclusions: Based on these findings, we propose that the efficacy of many cancer therapies, which are type I IFN-dependent, should be greatly improved by combination with TGFβ blockade. Disclosure Information: N. Bercovici: None. M.V. Guérin: None. F. Regnier: None. J.M. Weiss: None. V. Feuillet: None. L. Vimeux: None. G. Altan-Bonnet: None. E. Donnadieu: None. A. Trautmann: None.